NUTRITIONAL COMPOSITION OF SEVEN COMMERCIALLY IMPORTANT FRESHWATER FISH SPECIES AND THE USE OF CLUSTER ANALYSIS AS A TOOL FOR THEIR CLASSIFICATION - F. Jabeen; A. S. Chaudhry (Journal of Animal and Plant Sciences, 2016)
This study aimed to investigate the chemical composition and amino acid (AA) profile of seven freshwater fish species representing two mean live-weights inhabiting River Indus. For this purpose chemical composition was analysed by standard methods and amino acids were determined with an amino acid analyser (Biochrom-30 ion-exchange analyser). The fish species and live-weights differed significantly (P<0.01) for various nutrient compositions. Total fat and ash contents in all analysed fish species were higher in high weight (W2) than low weight (W1) category, while crude protein and total carbohydrates were higher in W1 than W2 category. These fish species contained most essential AA and particularly Lysine. Generally more amino acids were recorded in W1 than W2category. Cluster analysis showed that carnivorous fish species (A. oar sarwari, C. marulius and W. attu) were more similar to each other than herbivorous fish species (L. rohita and C. mrigala), while these differed from omnivorous fish species (C. carpio and O. mossambicus) with respect to amino acid contents. These fish offered good nutritional values and could be consumed to promote health and perhaps disease prevention in human beings.
Keywords: Amino acids; chemical composition; freshwater fish; nutritional value